Representasi Feminisme dalam Serial Film The Queen’s Gambit: Analisis Semiotika John Fiske - Ramadana, Alvian; Pujiyanto, Pujiyanto; Cendekia, Dhara Alim (Journal of Language Literature and Arts, 2024)
Gender inequality is a serious problem in the world that gives rise to feminist thought. Mass media such as series represent the reality of life to convey messages such as the issue of feminism. The Queen's Gambit is a series that tells the story of Beth Harmon, an intelligent woman who takes part in a chess match between men. This study uses a descriptive qualitative approach with the collection of observational data as primary data, interviews and documentation as secondary data. This study uses John Fiske's semiotic analysis by analyzing reality and representation to get the ideology of feminism in the main character of this series. The results of the study there are five scenes that represent feminism. The results of this study indicate the reality code in this series through appearance, costume, make-up, behavior, environment, speech, gesture, and facial expressions. Code representation such as camera, lighting, editing, music, sound effects, narration, conflict, character, action, and dialogue, as well as ideological code, there are feminist ideologies such as women's intellectuality, women's rights and responsibilities, women work to achieve transformation, rejection of women's existence under men, and women's representation in achieving social transformation in society.